2014
DOI: 10.1002/2014jb011324
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of methane hydrate‐bearing sediments and surrounding mud recovered from Nankai Trough wells

Abstract: This paper presents the measurement of the thermal constants of natural methane hydrate-bearing sediments and mud layer samples recovered from wells. Core samples were recovered from the Tokai-oki test wells (Nankai Trough, Japan) in 2004. The thermal conductivity, thermal diffusivity, and specific heat of the samples were simultaneously determined using the hot-disk transient method. The thermal conductivity of natural hydrate-bearing sediments decreased slightly with increasing porosity. In addition, the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 34 publications
3
36
1
Order By: Relevance
“…Goto and Matsubayashi (2009) suggested that each rock-forming mineral has its own thermal characteristics and the thermal properties of bulk sediments can be estimated by using mineral contents and porosity. However, the semi-quantitative evaluation in this study did not include the amount of unidentified minerals, glassy matrix, and humic substances, and thus it is further required to quantitatively measure these contents, together with the direct measurement of sediment thermal properties for data calibration (e.g., Muraoka et al, 2014).…”
Section: Bulk Mineralogymentioning
confidence: 99%
“…Goto and Matsubayashi (2009) suggested that each rock-forming mineral has its own thermal characteristics and the thermal properties of bulk sediments can be estimated by using mineral contents and porosity. However, the semi-quantitative evaluation in this study did not include the amount of unidentified minerals, glassy matrix, and humic substances, and thus it is further required to quantitatively measure these contents, together with the direct measurement of sediment thermal properties for data calibration (e.g., Muraoka et al, 2014).…”
Section: Bulk Mineralogymentioning
confidence: 99%
“…Muraoka et al 16 measured natural hydrate-bearing sediment cores recovered from Nankai Trough wells. They tested simple thermophysical models and concluded that the distribution model (geometric mean model) is suitable for estimating the thermal conductivity of hydrate-bearing sediments comprising sand, water, and MH.…”
Section: Introductionmentioning
confidence: 99%
“…Freezing occurs top down and results in the development of a crust that is ice rich. Silicates are a minor component of the mixture, and thus their impact on the thermal conductivity is small; see the supporting information, for example,Dai et al (2015),Durham et al (2010),Grimm and Mcween Jr (1989),Grindrod et al (2008),Muraoka et al (2014),Opeil et al (2010),Schofield et al (2014), Clathrates may represent the dominant form of water at pressures of a few MPa.…”
mentioning
confidence: 99%